Analysis of Critical Thinking Ability, Motivation and Achievement of Students In The Department of Islamic Religious Education - Muhammad Fahrurrozi; Nurul Yakin (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The quality of education in Indonesia still needs improvement, especially for educators to improve critical thinking skills and problem solving. The role of education is synonymous with the quality of human resources (HR) in society. To form human resources that have good quality, Indonesia needs to improve the concept of education because good education will also form good human resources. This study aims to determine (1) critical thinking skills, (2) learning motivation, and (3) student learning outcomes majoring in Islamic Religious Education at the State Islamic University of Mataram. This research is a type of quantitative research. Sampling was conducted on 40 students, consisting of 20 male and 20 female students in Islamic religious education courses. Research data collection techniques are divided into two types: data in the form of critical thinking skills and learning outcomes are obtained using test question instruments. In contrast, research data on learning motivation is obtained using non-test instruments in the form of questionnaires. All the data obtained in the research was then analyzed descriptively, and a comprehensive description of the data obtained in the research was provided. The results of the study show that (1) the critical thinking skills of students in Islamic religious education courses are in the moderately critical category but have different averages between male and female students; (2) the learning motivation of students in Islamic religious education courses is equally in the high category but has different averages between male and female students; and (3) the learning outcomes of Islamic religious education students are in the very good category for college students and good for female students.